Biology of Trichogramma marandobai and T. manicobai (Hymenoptera: Trichogrammatidae) in eggs of Erinnyis ello (Lepidoptera: Sphingidae) - Carvalho,Leidiane Coelho (2022)
ABSTRACT Parasitoids of the genus Trichogramma are promising for the biological control of insect pests in several crops, including cassava, which is severely attacked by Erinnyis ello L., 1758 (Lepidoptera: Sphingidae). Evaluating the biological aspects of these parasitoids to understand their dynamics is an important step towards the implementation of this control strategy in the field. Thus, our objective was to evaluate the biology of Trichogramma manicobai Brun, Moraes & Soares, 1984, and T. marandobai Brun, Moraes & Soares, 1986 in E. ello eggs. The parasitoids were obtained by collecting E. ello eggs from a commercial production of cassava, and the host’s eggs were obtained from laboratory and greenhouse rearings. The average duration of a generation (T), net reproduction rate (R0), intrinsic rate of increase (rm), and the finite rate of increase (λ) were estimated, and from these, the fertility life table was calculated. The results indicated that T. marandobai has both higher net reproduction rate and a higher intrinsic rate of increase as well as requires less time to double its population than T. manicobai. Thus, T. marandobai has potential for natural and conservative biological control of E. ello. In addition, its potential in applied biological control should be evaluated through studies on the viability of its mass rearing in alternative hosts and its dispersion behavior in the field.